ANALYSIS NINTH GRADE STUDENTS’ LEARNING STYLE AT SMPN 9 TARAKAN - Alya, Nurul Rezky; Setyawan, Farid Helmi; Effendi, Norman (Borneo Journal of English Language Education, 2022)
This study aimed to determine students’ learning style in ninth grade at SMPN 9 Tarakan. This research is a qualitative descriptive research. The targets of this study were teachers and students of SMPN 9 Tarakan. Data collection techniques used questionnaires and observations. From the data collected, based on the results of data analysis, it stated that class IX students who were involved in learning process tend to have a visual learning style. Students who had a visual learning style of 57%, auditory percentage of 13%, and kinestics of 30%. So from the results of this study it can be concluded that class XII students who take online learning tend to have a visual learning style.